2016
DOI: 10.1017/s1751731115002888
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of ruminal buffering systems to pH regulation in feedlot cattle fed either low- or high-forage diets

Abstract: The relative contribution of ruminal short-chain fatty acid (SCFA) absorption and salivary buffering to pH regulation could potentially change under different dietary conditions. Therefore, the objective of this study was to investigate the effects of altering the ruminal supply of rapidly fermentable carbohydrate (CHO) on absorptive function and salivation in beef cattle. Eight heifers (mean BW ± SD = 410 ± 14 kg) were randomly allocated to two treatments in a crossover design with 37-day periods. Dietary tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…Therefore, the higher feed intake might have contributed to the intermediate ruminating time observed during MS wk 4. Ruminating enhances ruminal pH by stimulating saliva secretion because increased saliva secretion buffers the rumen content by direct neutralization of VFA [21,22]. Besides inducing cows to alter chewing and sorting behaviour to alleviate ruminal pH, feeding diets moderate in peNDF may also promote the growth of the ruminal papillae and adaptive events of ruminal microbiota [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the higher feed intake might have contributed to the intermediate ruminating time observed during MS wk 4. Ruminating enhances ruminal pH by stimulating saliva secretion because increased saliva secretion buffers the rumen content by direct neutralization of VFA [21,22]. Besides inducing cows to alter chewing and sorting behaviour to alleviate ruminal pH, feeding diets moderate in peNDF may also promote the growth of the ruminal papillae and adaptive events of ruminal microbiota [23].…”
Section: Discussionmentioning
confidence: 99%
“…the production of saliva, the generation and absorption of volatile fatty acids (VFA), the type and level of feed intake, and the exchange of buffer through the ruminal epithelium [28]. In the used in-vitro system most likely the pH was reduced due to the formation of VFA [2729] and lactic acids [27,28] during fermentation and accumulation of these acids [30]. As a weak acid, these organic acids rapidly dissociate and release a proton and thereby decrease pH under most circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…While such variations could be driven by the composting process, it could also be due to initial differences in manure microbiota composition, determined by the diet of and gut microbiota composition of animals (Hussein et al, 2017;Chen et al, 2019). For example, previous studies have shown that the bovine feed contains more crude fiber, while chicken feed has higher contents of proteins and antibiotics (Sapkota et al, 2007;Chibisa et al, 2016). In general, carnivores consume food with significantly higher protein content than herbivores (Wilder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%